Food And Drink Advertising Analysis On Television: Structure And Language Functions - Wahyuni, Sri (Andalas International Journal of Socio-Humanities, 2019)
The current research focuses on the discourse analysis of the food and drinks advertisement. The data were collected from television advertisement by using observational method. The analysis is based on the qualitative approach by focusing the analysis on the discourse approach. Data of this study in the form of words, phrases, clauses, and sentences in food and beverage advertisements on television. The result of the analysis shows that the emotional aspect was frequently used to engage the costumers to the product. Some advertisements also use foreign language to give a good impression to the costumer. From the result of the analysis, it can be inferred that food and drinks advertisement not only provided information and about the product but also reflect the cultural value of the costumers.